The socio-demographic determinants of smoking and alcohol consumption: a cross sectional study in Penang, Malaysia. - Cheah, YK (Penerbit UKM, 2014)
The primary objective of the present study was to investigate the impact of socio-demographic factors on smoking and alcohol consumption among adults in Penang (Malaysia). A cross-sectional primary survey data with 398 respondents was used for analysis. The present study applied logistic regression models to examine the factors affecting the odds of smoking and alcohol consumption. The results showed that gender, ethnicity and education could significantly affect smoking. In particular, males (OR: 26.678) had a higher likelihood of smoking compared to the females, whereas Chinese (OR: 0.177), Indians/others (OR: 0.331) and individuals with tertiary education (OR: 0.258) had a lower likelihood of smoking than others. In terms of alcohol, gender, ethnicity and marital status were found to have a significant influence on the likelihood of alcohol consumption. Specifically, males (OR: 5.051), Chinese (OR: 37.796) and Indians/others (OR: 10.863) were more likely to consume alcohol than others, while married individuals (OR: 0.380) were less likely to consume alcohol than unmarried individuals. Based on the findings of the present study, numerous population-based intervention measures were suggested.